The Policy recommendations on health safety measures for earthquake situations in Thailand - Chaitiang, Narong (Public Health Policy and Laws Journal, 2025)
This article is a study of health safety measures and earthquake warning systems in Thailand. The researcher studied various health safety measures published related to the earthquake on March 28, 2025. The effects of the earthquake resulted in injuries and deaths from the collapse of buildings, damages to infra-structures for public utilities, fires, or electrical short circuits, causing injuries or deaths to people. Houses and buildings were damaged, unable to live in or worked in. There were mental health problems, such as stressed. Key points: The disaster management level in the case of earthquakes has been announced to be raised to disaster management (Level 3) in accordance with the National Disaster Prevention and Mitigation Plan 2021-2027. The government policy will be implemented, as well as coordinated implementation, assessment, situation monitoring, surveillance, and analysis, to provide opinions to the Prime Minister for unified command. Policy implications: In the future, an early warning system must be developed. and used in combination with Cell broadcast (emergency warning system), which can be sent by relying on the Cell. The important thing is, everyone must know how to survive.